Transformation of Pedagogical Communicative Competence during Creation Digital Online Courses - Grunis, Maxim L.; Golovanova, Inna I.; Kirilova, Galiya I.; Levina, Elena Y.; Sizova, Zhanna M. (Contemporary educational technology, 2021)
The purpose of this work is to identify the transformations of communicative functions. These functions are associated with the subjects of communication in both fields: in pedagogical and organizational, also in the instrumental and design once during the process of creating digital video recordings for online courses. Questionnaires, observation, and factor analysis were used as research methods. It helped to formulate a popularity rating of digital tools for future teachers. The study was conducted at the Institute of Psychology and Education of Kazan (Volga region) Federal University. The study involved 120 people: teachers developing online courses and students studying at the pedagogical educational programs. Transforming indicators of pedagogical communicative competence are highlighted. These indicators are needed to be emphasized when improving teacher training. It will help future teachers to be able to effectively carry out their activities in digital educational environment. These indicators are: the ability to organize interactive cooperation during training, the ability to organize mutual exchange and development of students, the ability to create an open environment for analysis and improvement. The methodological aspects of the development of pedagogical communication functions in the dynamic environment of digital education and an interactive environment are disclosed on the basis of work with videos. Some recommendations for future teachers’ skills improving and development of training experience organization in the digital environment are given. These are a clearly-set-goal for educational video materials, adequate video content, skills for digital tools using, also the skill to choose adequate digital tools for a task fulfillment. The tool that can enhance enthusiasm, and stimulate students for productive work in a digital environment. The study allows improving video content and increasing the effectiveness of its use in the educational process. Also, the results of the experiment can become a basis for teacher training programs improving. Especially it can be useful for future teachers’ pedagogical communicative and digital competences development. The tasks developed within the frame of the research will be included in the assignments of pedagogical internship for pedagogical Master’s degree courses at the Institute of Psychology and Education of Kazan Federal University. These tasks for students include development and use of online courses with video materials.